A STUDY ABOUT THE IMPACT OF MEDICAL CERTIFICATES ON SECONDARY SCHOOL STUDENTS` PARTICIPATION TO PHYSICAL EDUCATION AND SPORT ACTIVITIES - Ioan Drăgoiu; Dumitru Irimia (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
"Life is movement, repose is death" is the essence of the idea according to which it is necessary to habituate children and young people, through physical education and sport, with a healthy and organised life, based on hygienic, ethical and moral principles. Our love for the young and the responsibility for forming healthy young people who are harmoniously developed, both physically and mentally, made us approach this topic which is meant to be a signal for all the people involved in the education and teaching of tomorrow` s future: family, school, society, government. The increasing number of the students who have medical certificates should worry us all and make us look for the causes and find the solutions to prevent this phenomenon from growing, find alternative and varied solutions to impede the effects of incipient diseases. It is well known that movement is one of the most important factors which builds, polishes and structurally maintains the organism. When we prevent a child from the physical education classes, we endanger the health of the teenager or growing young person, who is threatened by the whole spectre of physical and organic deficiencies. Physical exercise equally contributes to the forming of one` s strong personality, which is deprived of prejudices and inferiority complexes